Ferramenta educativa propulsora ao desenvolvimento rural sustentável : pesquisa ação sob avaliação da sustentabilidade a luz da metodologia MADERUS - Hahn, Keitilanger Grisa (2022)
With the advancement and popularization of technologies aimed at rural areas, as well as the growing demand for efficiency/effectiveness in the management of these properties, tools that help in leveraging become inevitable, becoming an ability to add knowledge to face the challenges that small rural properties are found. Thinking in this context, the objective of this study is to identify in the Southwest region of Paraná, specifically in the context of family farming, through the applicability of sustainability indicators, their weaknesses and to develop a web system as an online tool for contributing to sustainable rural development. Therefore, a study of the state of the art was carried out first, through a bibliographic study, characterizing the existing publications on the subject. The sources of information were extracted from the BDTD in the period from 2006 to 2020, the identified themes were shown to be interdisciplinary, with emphasis on public universities. Subsequently, the MADERUS methodology was used, in a sample of 21 properties associated with AFAPO, aiming to trace mainly the fragile ones of these small farmers, verifying the need for actions for their financial / economic management. From the analysis, it was possible to propose a website which is a possibility of communication, management and interaction in the virtual environment, that is, it is an electronic site built on the Internet. This can facilitate the discussion and dissemination of important themes in rural areas, such as the improvement of processes and financial controls in management. As a limitation and suggestion for future work, it has not yet been observed how its use took place among users to improve sustainability indices in favor of sustainable rural development.